2005
DOI: 10.1007/s00595-004-2947-6
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Discovery of Diaphragmatic Injury After Blunt Trauma: Report of Three Cases

Abstract: Blunt diaphragmatic injury is an increasingly common occurrence, frequently associated with considerable comorbidity. This injury is often missed at the time of the initial event, but may present some time later. We report three cases of diaphragmatic injury diagnosed 3 weeks, 6 months, and 12 years after the original diaphragmatic injury, respectively. Two of the injuries resulted from side-impact road traffic accidents and one followed a fall from a height. Gastrointestinal obstruction and respiratory compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Because the right diaphragm is protected by the liver, such injuries almost exclusively involve the left diaphragm [4-6]. Diaphragmatic ruptures may be revealed many years after the initial trauma, presenting as abdominal visceral herniation and complications such as strangulation and perforation [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Because the right diaphragm is protected by the liver, such injuries almost exclusively involve the left diaphragm [4-6]. Diaphragmatic ruptures may be revealed many years after the initial trauma, presenting as abdominal visceral herniation and complications such as strangulation and perforation [7]. …”
Section: Discussionmentioning
confidence: 99%
“…25 In the acute trauma setting, the associated injuries may preoccupy the surgeon, who will often miss coexisting diaphragmatic injuries. 27 Currently, the management of blunt trauma in the absence of hemodynamic instability has been trending toward a nonoperative approach. As a result of its subtle and potentially asymptomatic clinical presentation, the absence of obvious external deformities, and a lack of unequivocal and timely diagnostic methods at the time of initial trauma, delayed diagnosis of TDH have been reported in 30 per cent to 50 per cent of patients.…”
Section: Historical Overviewmentioning
confidence: 99%
“…As a result of several widely publicized fatalities and malpractice claims and the lack of uniform regulation of office-based practices, research efforts have begun to address some of the controversial issues and turn attention to patient safety in the office 3 4 5 6 7 8 . In 2003, Vila et al 9 compared 2 years of reported adverse events and concluded that the relative risk of complications and death was 10 times greater in the office-based practices compared to ASCs.…”
Section: Introductionmentioning
confidence: 99%